Drawing A complete guide - civardi, giovanni (Tunbridge Wells, Kent [England] Search Press, 2010)
"This is an essential book for anyone learning to draw, or wishing to improve their drawing. Starting with the basics of drawing techniques, Civardi gives expert advice on drawing portraits, the clothed figure, hands and feet and scenery, with sections on the importance of light and shade and on the nude. Civardi's technical advice and practical tips, accompanied by his own outstanding drawings, make this an invaluable resource for any artist"--Page 4 of cover
1 13
Keywords: Drawing -- Study and teaching; Drawing -- Technique